Impact of Chronic Exposure to Sublethal Doses of Glyphosate on Honey Bee Immunity, Gut Microbiota and Infection by Pathogens - Loreley Castelli; Sofía Balbuena; Belén Branchiccela; Pablo Zunino; Joanito Liberti; Philipp Engel; Karina Antúnez (Microorganisms, 2021)
Glyphosate is the most used pesticide around the world. Although different studies have evidenced its negative effect on honey bees, including detrimental impacts on behavior, cognitive, sensory and developmental abilities, its use continues to grow. Recent studies have shown that it also alters the composition of the honey bee gut microbiota. In this study we explored the impact of chronic exposure to sublethal doses of glyphosate on the honey bee gut microbiota and its effects on the immune response, infection by Nosema ceranae and Deformed wing virus (DWV) and honey bee survival. Glyphosate combined with N. ceranae infection altered the structure and composition of the honey bee gut microbiota, for example by decreasing the relative abundance of the core members Snodgrassella alvi and Lactobacillus apis. Glyphosate increased the expression of some immune genes, possibly representing a physiological response to mitigate its negative effects. However, this response was not sufficient to maintain honey bee health, as glyphosate promoted the replication of DWV and decreased the expression of vitellogenin, which were accompanied by a reduced life span. Infection by N. ceranae also alters honey bee immunity although no synergistic effect with glyphosate was observed. These results corroborate previous findings suggesting deleterious effects of widespread use of glyphosate on honey bee health, and they contribute to elucidate the physiological mechanisms underlying a global decline of pollination services.